Tethered Cord Syndrome - Samsul Ashari (Indoscholar, 2018)
Tethered cord syndrome (TCS) is a clinical condition of various origins, which comprises of progressive neurological, urological, and orthopaedic dysfunction, because of congenital fixation or tethering of the distal spinal cord by the terminal filum. It is believed that, if the filum elasticity is compromised by either fatty infiltration or abnormal thickening, the spine movement may cause stress upon the conus, resulting in TCS. Patients with symptomatic TCS can present with a wide variety of signs and symptoms in combination with cutaneous, orthopaedic, spinal, anorectal, and urological abnormalities. The common clinical presentations include the presence of cutaneous signs associated with open septal defects, neurogenic bladder with incontinence or urinary tract infection, leg or foot weakness, numbness and/or spasticity, differences in leg or foot length, deformities of the foot, spinal deformities, and back and leg pain. Neuroimaging is used to confirm when there is suspicion of TCS. Magnetic resonance imaging is the modality of choice in visualizing the level of the conus medullaris and for identifying a thickened and/or fatty filum. The fundamental goals of surgical intervention in TCS are to prevent future deficits in the asymptomatic patient and to improve or stabilize deficits in the symptomatic patient. These two goals are based on the fact that sectioning of the terminal filum can be done safely with minimal risk and a very low rate of morbidity. The reported complications of surgery are cerebrospinal fluid leakage (most common), wound infection, meningitis, bladder dysfunction, and neurological injury.